Design of Mechanical Pepper Sorting and Screening Equipment for Pepper Post Harvest Optimization - Irwan Setiawan Muthalib; S Asmal; A B R Indah; S Bahri; Mulyadi -; R Hanafi; K Amar; F Mardin; M Rusman; I Bakri; N Syamsul; R D Mudiastuti; S Mangenre; S Parenreng; M A Darmawan; N Tahir (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
The majority of pepper plantations are smallholder plantations that are managed in a traditional way and there is still a lack of technology in the management process at the farmers, as a result the development of pepper cultivation is very slow and even decreased production. Meanwhile, entrepreneurs also find it difficult to process their harvests because the pepper that comes in is mixed with other materials such as soil, peeled off peppercorns, dried leaves, stems, fibers and also some light or mild pepper. The purpose of this activity is to provide an understanding of automation technology to entrepreneurs, workers and farming communities so that pepper production can be optimized according to export quality. The implementation method is divided into 2 parts, the initial part includes the design and design of the sorting and sifting mechanization tools, the last part is the socialization stage that targets the public's understanding of the benefits of the introduced technology as well as the operating capabilities of the equipment. To measure the level of public understanding used pre and post test mechanisms. The results achieved after the pre and post tests were showed an increase in understanding of automation technology and how it used by the community, an increase of around 80%. Meanwhile, the level of understanding for export quality product standards is around 85%. Broadly speaking, public interest shows a positive and enthusiastic change towards the use of this sorting and sifting mechanization tool and in the future it can increase pepper production capabilities in order to streamline post-harvest processing time and export immediately, so that pepper entrepreneurs can meet market demand by utilizing automation system technology so that more efficient and effective.